Conventional (D-dimer) and potential (pentraxin 3 and sST2) biomarkers in long-term prognosis of adverse cardiovascular events in COVID-19 survivors without significant cardiovascular diseases - T. V. Kanaeva; N. A. Karoli (Кардиоваскулярная терапия и профилактика)
Aim. To determine the potential role of conventional and potential biomarkers in predicting major adverse cardiovascular events (MACE) in the long-term period after coronavirus disease 2019 (COVID-19).Material and methods. On the day of hospitalization, 112 inpatients with a confirmed diagnosis of COVID-19 were assessed for biomarkers such as high-sensitivity troponin T (hsTnT) and troponin I (hsTnI), N-terminal pro-brain natriuretic peptide (NT-proBNP), D-dimer, soluble tumorigenicity suppression protein (sST2) and pentraxin 3 (PTX3). COVID-19 survivors were followed for a median period of 366 [365; 380] days after discharge from the COVID hospital, assessing the incidence of MACE (myocardial infarction, pulmonary embolism, cerebrovascular accident, cardiovascular death).Results. During the one-year follow-up period, the study endpoints (MACE) were registered in 14 (12,5%) patients. Of the cardiovascular biomarkers studied, differences were found in the levels of both conventional (hsTnT, D-dimer) and potential biomarkers (sST2, PT3) in the groups of patients with and without MACE. Groups did not differ significantly in NT-proBNP and hsTnI levels (p>0,05). According to multivariate analysis, the strongest predictors of MACE development are body mass index >29,5 kg/m2 (Area Under The ROC Curve (AUC) 0,672, sensitivity 45%, specificity 23,9%, p=0,001), PTX3 >3,1 ng/ml (AUC 0,885, sensitivity 94,0%, specificity 82,1%, p=0,001), sST2 >36 ng/ml (sensitivity 92,9%, specificity 33%, p=0,001), D-dimer >0,4 μg/ml (AUC 0,787, sensitivity 93%, specificity 72,4%, p=0,049). A mathematical model based on the concentration of PTX3, sST2 and D-dimer biomarkers predicts MACE within 1 year after COVID-19 with a sensitivity of 92,9%, specificity of 61% and predictive accuracy of 90,5% (p<0,001).Conclusion. Determination of the concentration of biomarkers such as D-dimer, sST2, PT3 can be used to predict long-term MACE in patients after COVID-19.